GROWTH AND PRODUCTION OF BENGGALA GRASS (Panicum maximum cv. Trichoglume) WHICH IS PLANTED WITH THE LEGUM Alysicarpus vaginalis IN VARIOUS DOSES OF NITROGEN - R. S., Saifullah; Suryani, N. N.; Roni, G. K. (Jurnal Peternakan Tropika, 2019)
The study aimed to obtain information about the growth and production of Bengal grass ( Panicum maximum cv. Trichoglume) which is planted with the legume Alysicarpus vaginalis  in various doses of nitrogen. This research was carried out in the laboratory greenhouse of the Faculty of Animal Husbandry, Udayana University, for 8 weeks. The grass and legumes used were Bengal grass ( Panicum maximum cv. Trichoglume) and Alysicarpus vaginalis . The design used was a completely randomized design (CRD) split plot pattern main plots / main plot is the of Alysicarpus vaginalis legume: without legume (A0), 1 legume (A1), 2 legumes Alysicarpus vaginalis (A2), 3 legumes Alysicarpus vaginalis (A3), and subplots / subplots namely fertilizer dosage: without fertilizer (D0), 100 kg N ha -1 (D1), 200 kg N ha -1 (D2). There were 12 treatment combinations and repeated 3 times so there were 36 experimental units. The variables observed were plant height, number of leaves, number of tillers, number of branches, amount of interest, leaf dry weight, stem dry weight, root dry weight, dry weight of the flower, total forage dry weight, leaf / stem dry weight ratio, total root ratio ( top root ratio ) and leaf area per pot.The results of variance showed that the treatment had a no significant effecton all variables, while the fertilizer dosage factor has a significant effectof almost all observed variables. Based on the results of the study concluded that the mixed cropping between Panicum maximum cv. Tricholume grass planted with Alysicarpus vaginalis legumes with 200 kg N ha -1 fertilizer produces higher growth and production.  Keywords: legume grass association, Panicum maximum grass, legume  Alysicarpus vaginalis, nitrogen fertilizer